FUNDMENTAL ANALYSIS FOR STOCK PRICE VALUATION BY USING PRICE EARNINGS RATIO METHOD (Study at Mining Companies Listed on Indonesian Stock Exchange Year 2011-2013) - Rovi Wahyuningtyas; . Suhadak; Raden Rustam Hidayat (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
The research was conducted based on the misprice on the investment of stock. The misprice of investment on stock can be reduced with evaluate the reasonable of stock price by using fundamental analysis. The fundamental analysis that used in this research is Price Earnings Ratio (PER) method. The PER method aim to know the reasonableness of stock price with compare the intrinsic value of stock and the stock market price. The research is descriptive quantitative method. The research takes the sample on mining industry listed on Indonesian Stock Exchange period 2011-2013. Based on the analysis by using PER method, the result of the research shows that the stock of ANTM, PTBA, and TINS in 2011 until 2013 is undervalued, thus the investment decision is purchase the stock. Whereas, estimating the stock position in 2014 is overvalued. Therefore the investment decision is sell the stock. Stock of RUIS in 2011 and in 2014 estimated is overvalued thus the investment decision is sell the stock. Meanwhile, in 2012 until 2013 the stock of RUIS is undervalued and the investment decision is purchase the stock. Keywords: Fundamental Analysis, Intrinsic Value, Price Earnings Ratio.